Sosialisasi Pada Generasi Z Tentang Bahaya Napza Bagi Kesehatan Dan Sanksi Hukum Di Rumah Singgah SRMS Kota Medan - Syahrul Bakti Harahap; Alkausar Saragih; Bonanda Jafatani Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Generation Z (gen Z), is the term for the genartions born between 1997 and 2012, generally reperred two as “Gen Z” This generation emerged after the millennial generation and before the alpha generation. The danger oe Nafza for generation Z is very potential because this generation is prone to being influenced by the surrounding environment. So it is important for them to begiven useful knowledge ebout the dangers of Nafza and legal witnesses. Among the Nafza that this generation is boren with are those related to health and the future that influnces health.Community servis regarding Sosilaization to generation Z abouth dangers of Nafza for health and legal sanctions at the SRMS Halfway Hause, Medan City, White the aim of providing knowledge about the consecuences of drugs abuse for health and legal sanctions. As well as the community’s legal behavior patterens.The method of activity carried out in this community service is through lectures in interactive disscussions ti generations Z and the community, about haw to avoid the dangers of alcoholism and legal sanctions for narcotics abuse, in accordance whit Law Number 35 of 2009, Conserning Narcotics.